PENGARUH INFLASI, SUKU BUNGA DAN SEKTOR-SEKTOR EKONOMI TERHADAP INVESTASI DOMESTIK DI INDONESIA - Yusmarti, Keken; Amar, Syamsul (Universitas Negeri Padang, 2020)
This study aims to determine the effect of inflation, interest rates, primary economic sectors and secondary economic sectors on domestic investment in Indonesia. The type of descriptive and associative research which uses secondary data is the quarterly time series from 2008 to 2019. The data comes from related institutions and agencies. Using the method of multiple linear regression is to see the extent to which the independent variables affect the dependent variable. Generating conclusions: (1) inflation does not have a significant relationship to domestic investment in Indonesia (2) interest rates do not have a significant relationship to domestic investment in Indonesia (3) the primary sector economy has a significant influence on domestic investment in Indonesia (4) the secondary sector economy significant effect on domestic investment in Indonesia (5) inflation, interest rates, primary sector economy and secondary sector economy significantly influence domestic investment in Indonesia.Keywords: Investment inflation, interest rates, primary economic sector, secondary economic sector and Ordinary Lest Square (OLS)